Fuzzy risk assessment modelling of East Kolkata Wetland Area: A remote sensing and GIS based approach. (January 2016) - Sarkar, Soma; Parihar, Seema M.; Dutta, Amitava
Abstract: East Kolkata Wetland Area (EKWA), a Ramsar site, is suffering from long-term resource exploitation and land-use change. This paper presents a Fuzzy-based Risk Assessment Model (FRAM) using Remote Sensing and GIS tools to identify the areas with varying intensity of wetland conversion risk within EKWA. Model was developed through rule-based Fuzzy Inference System. 'Wetlands conversion rate', 'Canal proximity', 'Road proximity', 'Population density', 'Population growth rate', 'Infrastructure status', 'Livelihood status', and 'Social status' were the eight selected input indices for the model. The model was validated at two stages. For stage one, Fuzzy c-Means (FCM) classified satellite data for 2012 and 2014 were compared to detect the landuse change. In stage two, model relevance over thirteen study sites was studied through questionnaire-based field survey. It was found that FRAM has efficiently modelled and mapped the various levels of wetland risk zones of EKWA. Highlights: Developed Fuzzy Risk Assessment Model (FRAM) for East Kolkata Wetland Area (EKWA) to map wetland conversion risk spatially. FRAM was developed on Fuzzy Inference System, with eight input indices generated from twenty two indicators. The model identified five different risk zones, ranging from 'very high risk zone' to 'very low risk zone'. Model validation at two stages approves that FRAM has efficiently modelled and mapped the wetland risk zones of EKWA.